A non-normal paralindelöf screenable space - Kurosaki, Makoto (Topology Proceedings, 2025)
We give an another proof of Fleissner’s full set lemma using elementary submodels and show that a minor change of C. Navy’s space is a non-normal paralindelöf screenable space. This answers a question of S. Watson.